Semi-quantum key distribution with two classical users - Wu, Wan Qing; Sun, Chen Yang (Frontiers in Physics, 2022)
Semi-quantum key distribution (SQKD) is an important research issue which allows one quantum participant equipped with advanced quantum devices to distribute a shared secret key securely with one classical user who have restricted capabilities. In this paper, we propose a SQKD protocol which allows one quantum user to distribute two different private secret keys to two classical users respectively at the same time. Alice distributes two particle sequences from Bell states to Bob and Charlie respectively. Once the particles have been processed and returned, Alice can simultaneously detect reflected particles by Bob and Charlie based on Bellstate measurement and generate two different raw keys. This protocol save more time when multiple classical users request the quantum server for key distribution. Security analyses show that the presented protocol is free from several general attacks, such as the entangle-measure attack, the modification attack, the double CNOT attack, and so on. Compared with similar studies, the proposed scheme is more practical and flexible.